Revisiting the position of unfair contract terms in Malaysia - Ismail, Suzi Fadhilah; Ayob, Juhana; Che Suhaimin, Syazalia (Centre for Islamisation International Islamic University Malaysia, 2024)
Unfair contract terms are usually found in the consumer contract. In most cases, the standard form of contract is commonly referred to as a ‘take it or leave it’ contract because the terms are drafted by the traders and the consumer is unable to discuss the terms of the contract which contains unjust terms. This paper seeks to revisit the legal framework governing unfair contract terms in Malaysia, embracing relevant rules and statutes as well as landmark cases that are concerned with unfair contract terms. The position of law relating to unfair contract terms in the United Kingdom is also examined for comparative approach as the law of contract as applied in Malaysia is essentially adopted from common law. Doctrinal analysis is employed as the method throughout the writing up. The paper analyses and highlights some weaknesses in the current legislation, in particular selected provisions of the Consumer Protection Act 1999. It finally concludes with some recommendation to improve the current legal framework of unfair contract terms in Malaysia.